NPFs-mediated actin cytoskeleton: a new viewpoint on autophagy regulation - Yuan Dong; Chengshi Quan (Cell Communication and Signaling, 2024)
Abstract Macroautophagy/autophagy is a lysosome-dependent catabolic process induced by various cellular stress conditions, maintaining the homeostasis of cells, tissues and organs. Autophagy is a series of membrane-related events involving multiple autophagy-related (ATG) proteins. Most studies to date have focused on various signaling pathways affecting ATG proteins to control autophagy. However, mounting evidence reveals that the actin cytoskeleton acts on autophagy-associated membranes to regulate different events of autophagy. The actin cytoskeleton assists in vesicle formation and provides the mechanical forces for cellular activities that involve membrane deformation. Although the interaction between the actin cytoskeleton and membrane makes the role of actin in autophagy recognized, how the actin cytoskeleton is recruited and assembles on membranes during autophagy needs to be detailed. Nucleation-promoting factors (NPFs) activate the Arp2/3 complex to produce actin cytoskeleton. In this review, we summarize the important roles of the actin cytoskeleton in autophagy regulation and focus on the effect of NPFs on actin cytoskeleton assembly during autophagy, providing new insights into the occurrence and regulatory mechanisms of autophagy. Video Abstract